1968
DOI: 10.1111/j.1467-6494.1968.tb01490.x
|View full text |Cite
|
Sign up to set email alerts
|

Personality characteristics which differentiate creative male adolescents and adults1

Abstract: Creabve performance is generally viewed as a consequence of a complex mteracbon among such vanables as cogmbve capacibes, specific personahty charactensbcs, and mtercurrent environmental mfluences. Increasingly, the behef has grown among tiiose who are parbcularly concemed with the role of personahty that creabve performance is stimulated, facihtated, and mamtamed by the presence of a rather hmited and specifiable set of personahty characterisbcs and pattems shared by all creabve men If there were m fact a str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
1

Year Published

1976
1976
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 13 publications
2
15
0
1
Order By: Relevance
“…fi ne artists vs applied artists) lest intradomain differences cancel one another out and badly obscure overall fi ndings. Important studies in which the role of domain has been explicitly considered have also been reported by Parloff et al (1968); Anastasi & Schaefer 1969;Schaefer 1969aSchaefer ,b,c and 1972bSchaefer ,c, 1973Schaefer & Anastasi 1968;Helson 1968a;Rossman & Hom 1972;Korb & Frankiewicz 1979. It should be noted in this context that Schaefer's studies of biographical inventory correlates of creativity led him to develop fi eld-specifi c creativity scales (Schaefer 1970a) for his inventory.…”
Section: Increased Attention To Age-and Field-related Diff Erencesmentioning
confidence: 92%
See 2 more Smart Citations
“…fi ne artists vs applied artists) lest intradomain differences cancel one another out and badly obscure overall fi ndings. Important studies in which the role of domain has been explicitly considered have also been reported by Parloff et al (1968); Anastasi & Schaefer 1969;Schaefer 1969aSchaefer ,b,c and 1972bSchaefer ,c, 1973Schaefer & Anastasi 1968;Helson 1968a;Rossman & Hom 1972;Korb & Frankiewicz 1979. It should be noted in this context that Schaefer's studies of biographical inventory correlates of creativity led him to develop fi eld-specifi c creativity scales (Schaefer 1970a) for his inventory.…”
Section: Increased Attention To Age-and Field-related Diff Erencesmentioning
confidence: 92%
“…In an analysis of personality correlates associated with creativity in adolescent and adult men, Parloff et al (1968), for example, identified a factor they called "D isciplined Effectiveness" which correlated positively with indices of creative achievement in their adolescent males and negatively with indices of creative achievement in their adult males. This reversal was discussed at some length in terms of the relative importance of impulse control at certain stages of personal and professional development.…”
Section: Increased Attention To Age-and Field-related Diff Erencesmentioning
confidence: 98%
See 1 more Smart Citation
“…Amateur creative individuals are people who are at primary or secondary schools that can be more creative than their peers (Liang, 2002). Research has proven that students who have become experienced during their school times by making scientific experiments by their own attempts are more creative in their later professional lives (Parloff, Datta, Kleman, & Handlon, 1968;Segal, Busse & Mansfield, 1980;Mumford, Supinski, Baughman, Costanza & Threlfall, 2005;Simonton, 2008). It may not give correct results when scientific creativity is measured by measures prepared for measuring general creativity (Liang, 2002).…”
Section: Introductionmentioning
confidence: 96%
“…Correspondence and requests for reprints should be sent to Debdulal Dutta Roy Several studies have shown that the personality characteristics of creative artists vary with age (Parioff, Datta, Kleman, & Handlon, 1968), and several have found sex differences (Barron, 1972;Block, Block & Harrington, 1975;Getzels & Csikszentmihalyi, 1976;Schaefer, 1969). The present study collected data only from male experienced fine artists.…”
mentioning
confidence: 94%